Genotoxic assessment of cerium and magnesium nanoparticles and their ionic forms in Eisenia hortensis coelomocytes by alkaline comet assay. Issue 9 (24th May 2022) - Güneş, Merve; Yalçın, Burçin; Ali, Muhammad Muddassir; Ciğerci, İbrahim Hakkı; Kaya, Bülent
Abstract: The present study aimed to evaluate the genotoxic potential of cerium oxide (CeO2 ), magnesium oxide (MgO) nanoparticles and their ionic forms by alkaline comet assay. Eisenia hortensis were exposed to different series of concentrations (25, 50, 100, 200, and 400 μg/ml) of chemicals for 48 h to find LC50 . The LC50 for MgO and CeO2 NPs were 70 and 80 μg/ml. Whereas, the LC50 for their ionic forms were 50 and 70 μg/ml. To assess the potential DNA damage caused by the chosen chemicals, E. hortensis was further exposed for 48 h to the following concentrations, based on their respective LC50s : LC50/2, LC 50, and 2xLC50 . Comet scores demonstrated the significant increase ( p  < 0.05) in DNA damage at all concentrations, both for NPs and ionic forms in a concentration‐dependent manner. Findings of the present study revealed the genotoxic effects of CeO2 NPs, MgO NPs and their ionic forms on E. hortensis . Research Highlights: Genotoxic assessment of CeO2 and MgO NPs and their ionic forms was conducted. Characterization of NPs through electron microscopy and alkaline comet assay was performed on E. Hortensis . Highest DNA damage of CeO2 and MgO NPs was observed on earthworm. Abstract : Genotoxic effects of cerium and magnesium nanoparticles